(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
Gastronomic tourism is becoming an increasingly important consideration for visitors when choosing a vacation spot. For visitors, “gastronomy” is one of the primary motivations for visiting a specific region. As a result, “Gastronomic Tourism” has emerged as a novel form of tourism. However, there has been minimal research into food tourism, particularly in Uzbekistan. The fundamental goal of this study is to explore tourist motivation at a culinary tourism site in the travel market, as well as to evaluate gastronomy as a component of visitor motivation.